2010
DOI: 10.1074/jbc.m109.030023
|View full text |Cite
|
Sign up to set email alerts
|

β-Amyloid Causes Depletion of Synaptic Vesicles Leading to Neurotransmission Failure

Abstract: Alzheimer disease is a progressive neurodegenerative brain disorder that leads to major debilitating cognitive deficits. It is believed that the alterations capable of causing brain circuitry dysfunctions have a slow onset and that the full blown disease may take several years to develop. Therefore, it is important to understand the early, asymptomatic, and possible reversible states of the disease with the aim of proposing preventive and disease-modifying therapeutic strategies. It is largely unknown how amyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
123
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 164 publications
(146 citation statements)
references
References 49 publications
(61 reference statements)
23
123
0
Order By: Relevance
“…In addition, it was also demonstrated that Aβ reduced the magnitude of exocytosis and that the remaining synaptic vesicles displayed a much slower speed of endocytosis, thus inhibiting presynaptic function (Parodi et al, 2010). By using electron microscopy, these authors also reported that Aβ-treated neurons displayed reduced number of synaptic vesicles, especially those near the presynaptic active zones and a reduction in several presynaptic proteins (Parodi et al, 2010).…”
Section: Aβ At Presynaptic Level and Glial Cellsmentioning
confidence: 85%
See 1 more Smart Citation
“…In addition, it was also demonstrated that Aβ reduced the magnitude of exocytosis and that the remaining synaptic vesicles displayed a much slower speed of endocytosis, thus inhibiting presynaptic function (Parodi et al, 2010). By using electron microscopy, these authors also reported that Aβ-treated neurons displayed reduced number of synaptic vesicles, especially those near the presynaptic active zones and a reduction in several presynaptic proteins (Parodi et al, 2010).…”
Section: Aβ At Presynaptic Level and Glial Cellsmentioning
confidence: 85%
“…In addition, it was also demonstrated that Aβ reduced the magnitude of exocytosis and that the remaining synaptic vesicles displayed a much slower speed of endocytosis, thus inhibiting presynaptic function (Parodi et al, 2010). By using electron microscopy, these authors also reported that Aβ-treated neurons displayed reduced number of synaptic vesicles, especially those near the presynaptic active zones and a reduction in several presynaptic proteins (Parodi et al, 2010). Accordingly, presynaptic proteins such as SNAP-25, synaptophysin, and synaptotagmin were reduced in brains of patients with AD (Reddy et al, 2005) and in the hippocampus of Tg2576 mice 1 month after injection of Aβ into the third ventricle (Chauhan and Siegel, 2002 (Russell et al, 2012).…”
Section: Aβ At Presynaptic Level and Glial Cellsmentioning
confidence: 99%
“…A common hypothesis used to explain the toxicity induced by A␤ is the formation of amyloid pores in the plasma membrane. Regarding this, several studies from our and other laboratories support the notion that membrane disruptions are induced by A␤ [6][7][8][9][10][11][12][13]. Furthermore, A␤ perforation allows the entry of small molecules and ions, such as calcium, into the cells [6,7,12].…”
Section: Introductionmentioning
confidence: 85%
“…Regarding this, several studies from our and other laboratories support the notion that membrane disruptions are induced by A␤ [6][7][8][9][10][11][12][13]. Furthermore, A␤ perforation allows the entry of small molecules and ions, such as calcium, into the cells [6,7,12]. This sustained calcium influx increases the release in synaptic vesicles, leading to a delayed synaptic failure produced by vesicle depletion [6][7][8].…”
Section: Introductionmentioning
confidence: 89%
“…Aggregation of Aβ 1–42 at 5 μ m was achieved as previously described (Parodi et al ., 2010). Briefly, human Aβ 1–42 was dissolved with dimethylsulfoxide (DMSO) at 2.3 m m ; an aliquot of the 2.3‐m m solution was then dissolved in PBS to a final concentration of 80 μ m .…”
Section: Methodsmentioning
confidence: 99%